The Foundation of Understanding the Living al-Qur'an as a Reinforcement of Islamic Humanism in the Context of Civil Society - Ermita Zakiyah (LPPM Institut Pesantren KH. Abdul Chalim, 2023)
The purpose of this article is to provide an understanding to the public about the living al-Qur'an, which is sought to strengthen Islamic humanism in the context of civil society through the text and contextualization of the Qur'an. This is based on the fact that Indonesia has a majority Muslim population and should rely on understanding Islamic humanism with the Qur'an as a guide and a barometer of life. The method in this research is library research with analysis of the Koran as the primary source, the method used in analyzing is the maudhui interpretation method through the stages of collecting verses of the Koran related to humanism and using the asbabun nuzul approach and interpretation contextual when the verse was revealed. The result of this research is to provide an understanding of the living al-Qur'an as the main step to improving understanding of the verses of the Qur'an and strengthening Islamic humanism in the context of civil society in Indonesia so that the Qur'an can be applied in life, not only textually. But contextually, in Indonesian society.